The role of platelets in the pathogenesis of systemic sclerosis - Ramirez, Giuseppe A.; Franchini, Stefano; Rovere-Querini, Patrizia; Sabbadini, Maria Grazia; Manfredi, Angelo A.; Maugeri, Norma (Frontiers in Immunology, 2012)
Systemic sclerosis (SSc) is an inflammatory disease of unknown etiology characterized by widespread organ dysfunction due to fibrosis and ischemia. Its nebulous pathogenic background and the consequent absence of an etiological therapy prevent the adoption of satisfying treatment strategies, able to improve patients’ quality of life and survival and stimulate researchers to identify a unifying pathogenic target. Platelets show a unique biological behavior, lying at the crossroads between vascular function, innate and adaptive immunity, and regulation of cell proliferation. Consequently they are also emerging players in the pathogenesis of many inflammatory diseases, including SSc. In the setting of SSc platelets are detectable in a persistent activated state, which is intimately linked to the concomitant presence of an injured endothelium and to the widespread activation of the innate and adaptive immune system. As a consistent circulating source of bioactive compounds platelets contribute to the development of many characteristic phenomena of SSc, such as fibrosis and impaired vascular tone.